Ly6C(+) monocyte efferocytosis and cross-presentation of cell-associated antigens - Larson, S R (Cell Death Differ, 2016)
Recently it was shown that circulating Ly6C(+) monocytes traffic from tissue to the draining lymph nodes (LNs) with minimal alteration in their overall phenotype. Furthermore, in the steady state, Ly6C(+) monocytes are as abundant as classical dendritic cells (DCs) within the draining LNs, and even more abundant during inflammation. However, little is known about the functional roles of constitutively trafficking Ly6C(+) monocytes. In this study we investigated whether Ly6C(+) monocytes can efferocytose (acquire dying cells) and cross-present cell-associated antigen, a functional property particularly attributed to Batf3(+) DCs. We demonstrated that Ly6C(+) monocytes intrinsically efferocytose and cross-present cell-associated antigen to CD8(+) T cells. In addition, efferocytosis was enhanced upon direct activation of the Ly6C(+) monocytes through its corresponding TLRs, TLR4 and TLR7. However, only ligation of TLR7, and not TLR4, enhanced cross-presentation by Ly6C(+) monocytes. Overall, this study outlines two functional roles, among others, that Ly6C(+) monocytes have during an adaptive immune response.